Market Externalities of Large Unemployment Insurance Extension Programs - Rafael Lalive; Camille Landais; Josef Zweimüller (Center for Economic Studies and ifo Institute (CESifo), 2013)
This paper offers quasi experimental evidence of the existence of spillover effects of UI extensions using a unique program that extended unemployment benefits drastically for a subset of workers in selected regions of Austria. We use non-eligible unemployed in treated regions, and a difference-in-difference identification strategy to control for preexisting differences across treated and untreated regions. We uncover the presence of important spillover effects: in treated regions, as the search effort of treated workers plummets, the job finding probability of untreated workers increases, and their average unemployment duration and probability of long term unemployment decrease. These effects are the largest when the program intensity reaches its highest level, then decrease and disappear as the program is scaled down and finally interrupted. We use this evidence to assess the relevance of different assumptions on technology and the wage setting process in equilibrium search and matching models and discuss the policy implications of our results for the EUC extensions in the US.
Keywords: J65; J21; J22; 330; unemployment insurance; benefit extension; market externality; macro effects